Effects of air-perfused rucksack on physiological and perceptual strain during low-intensity exercise in a hot environment. Issue 2 (2nd April 2020) - Kajiki, Masanobu; Yamashita, Naoyuki; Ito, Ryo; Matsumoto, Takaaki
ABSTRACT: The upcoming Tokyo Olympic and Paralympic Games may be held amid extremely high wet-bulb globe temperature conditions. Many studies have focused on countermeasures to prevent the reduction in exercise performance in the heat. However, cooling strategies for managing heat stress of staff and spectators remain poorly understood. The present study investigated the effects of a lightweight fan cooling device, namely a commercially available air-perfused rucksack, on physiological and perceptual responses during low-intensity exercise in a hot environment. Ten males walked (5.5 km/h, 2.0% gradient) for 60 min in hot conditions (35°C, 50% relative humidity). All participants performed two trials with and without the air-perfused rucksack, respectively. Air was blown onto the upper back and neck via two fans attached on either side of the rucksack. Rectal temperature, neck skin temperature, heart rate, and physiological strain index were significantly lower during walking (P < 0.05) with the rucksack. Additionally, the ratings of perceived exertion, thermal sensation, and thermal comfort were significantly lower (P < 0.05) with the rucksack. These data suggest that the air-perfused rucksack may be effective for managing heat stress of staff and spectators at the Tokyo Olympic and Paralympic Games. Abbreviations: CON: control trial; ES: effect sizes; FAN: fan cooling trial; HR: heart rate; m Tsk : mean skin temperature; pre: pre-exercise; PSI: physiological strain index; RPE: rating of perceived exertion; SD: standard deviation; TC: thermal comfort; Tneck : neck skin temperature; Tre : rectal temperature; TS: thermal sensation